Bioethics as practice - Andre, Judith (Studies in social medicine., 2002)
Those who work in bioethics and the medical humanities come from many different backgrounds, such as health care, philosophy, law, social sciences and religious studies, and the work they do varies widely. Judith Andre offers a model to unify its diversity.